Variation of biochemical content in the almonds of the endemic Argan tree (Argania spinosa (L.) Skeels) populations in Morocco - Ayan, Sezgin; Abdaloğlu, Gülbahar; Laaribya, Said; Turfan, Nezahat; Yer Çelik, Esra Nurten; Ouhaddou, Halim; Alaoui, Assmaa (Bogucki Wydawnictwo Naukowe, 2023)
In this study, it was aimed to determine the variation of the biochemical characteristics of the argan [Argania spinosa (L.) Skeels] in natural distribution areas in Morocco. For this aim, it was used 13 populations, which are representative of the taxon on different sub-ecoregion in Morocco, to determine some biochemical compositions characters such as malondialdehyde (MDA), hydrogen peroxide (H2O2), proline, protein, flavonoid, phenol, glucose, sucrose, fructose, enzyme activities of superoxide dismutase (SOD), and peroxidase (POD) were analyzed. To determine variations among the population were analyzed using ANOVA. In addition, the phylogenetic relationship among the populations was revealed by Cluster Analysis. As a result of the research, significant differences were determined in terms of all parameters such as proline, protein, flavonoid, phenol, glucose, sucrose, fructose, MDA, H2O2, SOD, and POD of almond diversity among the populations. According to the Cluster Analysis, the results showed that the Tamanar population was relatively different from all other populations. The results obtained in the research confirm the high variety of different habitats in the natural distribution areas of argan in Morocco. The revealing of the diversity among the populations in the natural distribution area of this extremely degraded species is of primary importance for the conservation policies and sustainable use of the species.
Keywords: 15. Life on land